ChemInform Abstract: Synthesis, Crystal Structure, and Properties of the Ordered Double Perovskite Sr2CoOsO6. Issue 4 (28th January 2014) - Paul, Avijit Kumar; Reehuis, Manfred; Felser, Claudia; Abdala, Paula M.; Jansen, Martin
Abstract The new title compound is prepared by solid state reaction of a stoichiometric mixture of SrO2, OsO2, and Co3O4 (1.